Cardiovascular Effects of Trans-4-Methoxy-β-Nitrostyrene in Spontaneously Hypertensive Rats: Comparison With Its Parent Drug β-Nitrostyrene - Alves-Santos, Thayane Rebeca; Silva, Odair Alves; Moreira, Hicla Stefany; Borges, Rosivaldo Santos; Duarte, Gloria Pinto; Magalhães, Pedro Jorges Caldas; Lahlou, Saad (Frontiers in Pharmacology, 2019)
Previously, we showed that trans-4-methoxy-β-nitrostyrene (T4MN) induced higher vasorelaxant effects in small resistance arteries from spontaneously hypertensive rats (SHRs) in comparison with its parent drug, the β-nitrostyrene 1-nitro-2-phenylethene (NPe). To further our knowledge of the influence of introducing an electron-releasing group such methoxy in the para position of the aromatic moiety of NPe, we investigated the cardiovascular responses to intravenous (i.v.) injection of T4MN in SHRs and compared with those of NPe. In pentobarbital-anesthetized SHRs, intravenous (i.v.) bolus injection of T4MN (0.03-0.5 mg/kg) and NPe (0.03-3 mg/kg) induced dose-dependent bradycardia and hypotension, which were characterized in two periods (phases 1 and 2). Magnitude of these responses was significantly higher for T4MN compared with NPe. The first rapid component (phase 1) elicited by both T4MN (0.3 mg/kg) and NPe (3 mg/kg) was abolished by cervical bivagotomy or perineural treatment of both cervical vagus nerves with capsaicin, but remained unaltered by i.v. pretreatment with capsazepine or ondansetron. Phase 1 was not recorded when NPe or T4MN was directly injected into the left ventricle. In conscious SHRs, NPe (3 mg/kg, i.v.) and T4MN (0.3 mg/kg, i.v.) evoked rapid hypotensive and bradycardiac effects which was abolished by i.v. pretreatment with methylatropine. In conclusion, i.v. treatment of SHRs with NPe and T4MN induced a vago-vagal hypotensive and bradycardic reflex that involves the activation of neither vanilloid TRPV1 nor 5-HT3 receptors located on vagal pulmonary sensory nerves. The phase 2 hypotensive response to i.v. NPe and T4MN seems to result, at least in part, from their direct vasodilatory effect on the peripheral smooth muscle. Introduction of a methoxy group into the aromatic moiety apparently stabilizes NPe, thereby enhancing its cardiovascular effects